Book Review: Digital Storytelling as Translanguaging: A Practical Guide for Language Educators - Mihat, Warid (The English Teacher, 2026)
In recent years, the chant ‘multilingual turn’ and the growing attention to multimodality in English Language Teaching have brought translanguaging to the forefront of pedagogical debate. While translanguaging, a term often understood as a strategic use of learners’ full linguistic repertoires, has been widely theorised, its classroom implementation remains a challenge for many educators. In the book, Digital Storytelling as Translanguaging: A Practical Guide for Language Educators, Linville and Vinogradova (2024) provide a framework for using digital storytelling as multimodal tools to foster equity and learner agency in the increasingly diverse 21st Century classrooms. Through this book, the authors show how audio, visual, and students’ dynamic language repertoire can be used as tools to reduce the impacts of passive banking model in education.
Keywords: Multilingualism, Multilingual Students, translanguaging, pedagogy, Literary Practices; dialogic reading, digital storytelling, intramental dialogue, intermental dialogue